A novel diagnosis indicator for rub-impact of rotor system via energy method. (15th February 2023) - Zhang, Xiantao; Yang, Yongfeng; Ma, Hui; Shi, Mingming; Wang, Ping
Highlights: The novel diagnosis indicator based on the time-averaged power flow is proposed, and the accuracy of the proposed indicator is verified by experiments. The transient energy chaning trend under different rub-impact condition is obtained. The diagnosis indicator has a good effect on the theoretical application of the pratical rotor system and it can detect the severity of rub-impact faults. Abstract: Rub-impact between rotor and stator is a common mechanical fault for rotating machinery, which will bring risks into the normal operation. Detecting the severity of the rub-impact fault accurately is helpful to prevent serious mechanical accidents. However, traditional methods based on the displacements or spectrum analysis may occur some differences toughly distinguished with the naked eyes, and eventually cause inaccurate judgment in some cases. To overcome such shortcomings, this paper proposes a novel diagnosis indicator for rotor systems with rub-impact fault. The dynamic model of the rotor system is established by the finite element method. Based on the vibration power flow theory, the novel indicator is developed by considering the force, velocity, and phase information in a time interval (Time-averaged input power flow). Through theoretical analysis of the rub-impact faults, the energy responses and the law between input power and rub-impact of the rotor system are obtained. Meanwhile, the severity detection of faults by using the proposed indicator has been achieved. The corresponding tests are carried out to validate the accuracy of the theoretical results. The experimental results reveal the proposed indicator can help judge the different severity of rub-impact faults, which means the lower time-averaged input power flow indicates a serious fault. To evaluate the application effect of the proposed indicator in engineering, the rub-impact fault of the GE-T700 power turbine rotor is investigated through theoretical analysis. And the diagnosis results are consistent with the above consequences. The conclusions achieved in this paper can provide a reference for fault diagnosis of rotor systems in engineering practice.